The pathology of cornea in Tangier disease (familial high density lipoprotein deficiency). Issue 5 (May 1996) - Winder, A F; Alexander, R; Garner, A; Johnston, D; Vallance, D; McCreanor, G; Frohlich, J
Abstract : AIMS: To clarify the underlying causes of corneal opacification in Tangier disease. METHODS: Both corneas were removed at death from a 62 year old man with Tangier disease, and were examined by direct and transmission electron microscopy, histochemistry, biochemical analysis by thin-layer and gas-liquid chromatography after extraction, and by differential scanning calorimetry. RESULTS: Membranous inclusions in the stroma were seen on transmission electron microscopy. Direct analysis confirmed enrichment with phospholipids and cholesterol, with acyl patterns and proportions as ester broadly similar to those of normal cornea. Tangier cornea showed major thermotropic phase transitions in the range 28-37 degrees C, peak 30-33 degrees C, extending above profiles of normal clear cornea and without the complexity of those seen with cornea with heavy arcus involvement. CONCLUSIONS: Lipid accumulation underlies corneal opacification in Tangier disease. The excess material is mainly phospholipid and cholesterol esters. As at other sites which are below body core temperature, notably tonsil, accumulation may be enhanced by local impaired mobilisation of material as the phase transitions of the excess lipid present extend above ambient corneal temperatures.